Digital technology and caregiver training for older persons: Cognitive and affective perspectives. Issue 8 (2nd August 2016) - Zheng, Robert; Hicken, Bret L.; Hill, Robert D.; Luptak, Marilyn; Daniel, Candice M.; Grant, Marren; Rupper, Randall
ABSTRACT: This research project included two studies that investigated (a) differences between technology use in tech-knowledgeable and less tech-knowledgeable older persons, (b) cognitive and affective variables and their association with the application of technology, and (c) the implications of these variables on the design of remote-delivered caregiver education. Study 1 findings suggested that high technology (e.g., Internet delivered education) reduced stress among the tech-knowledgeable group. In Study 2, which focused on the less tech-knowledgeable group, neither high technology (e.g., telehealth-delivered education) nor low technology (e.g., phone-delivered education) was associated with the cognitive and affective measures used in the study. Implications in the training of older caregivers with digital technology are discussed for negotiating the affective and cognitive features in remote delivered caregiver eduational protocols.